ANALISIS POTENSI PARIWSATA DAN PERAN MASYARAKAT DESA WISATA MOLINOW, DI KABUPATEN MINAHASA SELATAN - Sambeka, Vesty Like; Bawole, Merryany Theovanny; Sinolungan, Linda E. M; Lumare, Mercy A (PolimdoSains, 2024)
The aim of this research is to analyze the potential and role of the community in theMolinow tourist village, South Minahasa Regency. This research uses observation, interviewand documentation methods in South Minahasa Regency. In particular, Molinow Village hasbecome a tourist village, with the Tanjung Molinow Beach tourist attraction, equipped withfacilities that support recreation in that place. Molinow Tourism Village is a new TourismVillage which was inaugurated on April 8 2022 along with the Tanjung Molinow Beach touristattraction by the deputy Regent of South Minahasa based on the decision of the Ministry ofVillages, Development of Disadvantaged Regions and Transmigration (KEMENDESA) in2020. The research results show that the Molinow tourist village has tourism potential whichis beautiful, especially on Tanjung Molinow beach, which is the tourist center. With theexistence of the Malinow tourist village, the community's economic turnaround is starting tobe felt. The village community hopes that the Malinow tourist village can develop and becomea tourist village visited by many tourists and become a tourism actor who has a role in creatinga conducive and comfortable environment for its visitors. With the existence of a tourismawareness group, the community plays a more active role in developing the Molinow touristvillage. Tourism awareness groups must be supported with full awareness to make the Molinowtourist village a safe, orderly, clean, cool, beautiful, friendly and memorable village.